2010
DOI: 10.1111/j.1538-7836.2010.03831.x
|View full text |Cite
|
Sign up to set email alerts
|

Out of hospital treatment of acute pulmonary embolism in patients with a low NT‐proBNP level

Abstract: http://clinicaltrials.gov/ct2/show/NCT00455819.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 38 publications
6
70
1
7
Order By: Relevance
“…The remaining 11 studies were included in our systematic review. Eight were prospective cohort studies [8,[11][12][13][31][32][33][34]] and 3 were randomized controlled trials (RCT's) [16,17,35]. Furthermore, 2 studies did not report outcomes at 3 months and could not be used in our pooled meta-analysis [12,13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 11 studies were included in our systematic review. Eight were prospective cohort studies [8,[11][12][13][31][32][33][34]] and 3 were randomized controlled trials (RCT's) [16,17,35]. Furthermore, 2 studies did not report outcomes at 3 months and could not be used in our pooled meta-analysis [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that outpatient management or early discharge of patients with acute PE is safe and effective [8][9][10][11][12][13]. Two systematic reviews suggested that patients with acute PE treated as outpatients had low incidences of major bleeding, recurrent venous thromboembolism (VTE), and mortality [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cut-off levels for D-dimer were based on previous studies in which D-dimer with a cut-off level >3,000 lg/l FEU was a strong predictor for short-term [28,29]. The chosen cut-off level for NT-proBNP of >500 pg/ml was based on our previous study in which outpatient treatment of PE-patients was based on NT-proBNP levels <500 pg/ml [30]. The addition of age, gender, or cardiopulmonary disease did not improve the model.…”
Section: Prognostic Model For Adverse Clinical Eventsmentioning
confidence: 99%
“…Some clinical severity classifications have been made as prognostic indicators in APE (4,5). There are also publications which indicate that biochemical indicators such as troponins, heart-type fatty acid-binding protein, brain natriuretic peptide or N-terminalproBNP and right ventricular dysfunction may be prognostic factors (6)(7)(8)(9)(10). Neutrophil-Lymphocyte Ratio (NLR) is a readily measurable laboratory marker used to evaluate systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%